Analisis Daya Tahan Lama Simpan Pada Bakso Dengan Penambahan Tepung Asap Melalui Proses Mikroenkapsulasi - Anin, Desi Fatima; Abrina Anggraini, Sinar Perbawani; Iskandar, Taufik (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Bakso is a processed meat product that is made by grinding it then mixing it with flour and cooking spices and then boiling it until cooked. However, meatballs have a relatively short shelf life when stored at room temperature, so preservatives are needed that are safe for consumption and can increase the shelf life of these meatballs. The preservative offered is the manufacture of liquid smoke by the pyrolysis process. The use of liquid smoke is not only limited to liquid smoke because it is considered impractical, so it is necessary to develop technology to protect the active components and facilitate its handling by making liquid smoke powder using maltodextrin as a carrier medium. This study aims to determine the optimal drying temperature in the microencapsulation process of smoked flour and the optimal storage time for the quality of food product preservation. There are 2 variables in this study, namely fixed variables and changing variables. Fixed variables included 2.5 kg coconut shell weight and 30% maltodextrin while changing variables included drying temperature (1350C, 1400C, 1450C 1500C) with shelf life (0, 2, and 4 days) and analysis parameters included moisture content and protein content. Smoked flour made by the microencapsulation method is proven to preserve food ingredients. This is because smoked flour has an acid content that can inhibit bacterial growth. Smoked flour with a concentration of 5% and a temperature of 135 â„ƒ is the most effective way to preserve meatball dough because it can provide a long shelf life of 3 days.